2010
DOI: 10.1111/j.1467-8535.2009.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Which do students prefer to evaluate their essays: Peers or computer program

Abstract: The purpose of this study was to investigate problems and potentials of new technologies in English writing education. The effectiveness of automated writing evaluation (AWE) (MY Access) and of peer evaluation (PE) was compared. Twenty-two English as a foreign language (EFL) learners in Taiwan participated in this study. They submitted their draft to MY Access, received feedback from this automated grading system and then made some revision. In addition to the AWE, they also had peer revision in writing class.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 38 publications
5
97
0
Order By: Relevance
“…However, the research into the use of AES/AWE applications paints a confusing picture, with some studies reporting favourable results (Coniam, 2009;Hutchison, 2007) while others report negative or mixed results (Lai 2010;Lee et al, 2009;Tuzi, 2004), with factors such as individual writing ability, the pedagogy adopted and the particular AES/AWE application influencing the results (Lee et al, 2009). For example, less trained writers faced difficulties in using revision tools (Kozna and Johnston, 1991); learners using My Access were dissatisfied with the grade the software awarded them, and with both the accuracy and clarity of feedback on content and the rhetorical aspects of their writing (Chen and Cheng, 2006).…”
Section: The Effectiveness Of Aes/awe Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the research into the use of AES/AWE applications paints a confusing picture, with some studies reporting favourable results (Coniam, 2009;Hutchison, 2007) while others report negative or mixed results (Lai 2010;Lee et al, 2009;Tuzi, 2004), with factors such as individual writing ability, the pedagogy adopted and the particular AES/AWE application influencing the results (Lee et al, 2009). For example, less trained writers faced difficulties in using revision tools (Kozna and Johnston, 1991); learners using My Access were dissatisfied with the grade the software awarded them, and with both the accuracy and clarity of feedback on content and the rhetorical aspects of their writing (Chen and Cheng, 2006).…”
Section: The Effectiveness Of Aes/awe Applicationsmentioning
confidence: 99%
“…Students rated the electronic feedback superior for "markscheme clarity, feedback legibility, information on deficient aspects, and identification of those parts of the work where the student did well", and the lecturers reported taking less time to mark when using the software. Lai (2010), however, investigated preferences among English as a foreign language (EFL) learners in Taiwan for computer-based using MY Access or peer feedback and found that although both forms were considered effective the learners tended to express a preference for peer feedback over computer feedback. Matsumara (2004) investigated the influence of computer-anxiety on the preferences of Japanese students for face-to-face teacher feedback, online teacher feedback, and peer feedback in EFL writing classes.…”
Section: Students' Feedback Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, students can make progress in linguistic performance, writing competence and self-efficacy with the help of automated feedback (Yang, 2004;Zhou, 2013;Yang & Dai, 2015). Meanwhile researchers also discover weaknesses in automated feedback, for example, it may appear mechanical, inaccurate and repetitive, lessening students' active adoption (Lai, 2010;Wei, 2015;Morch et al, 2017). Although its efficacy needs more empirical studies, there is no denying that automated feedback has gaining momentum in L2 writing practice.…”
Section: Research Of Feedbackmentioning
confidence: 99%
“…Some students do not like the idea of a computer scoring their work. Lai (2010) found that students preferred their writing be evaluated by a peer rather than by an AES. Students often worry that an AES cannot understand novel ideas and concepts, or properly grade answers that were not part of its training (Landauer, Laham & Foltz, 2000).…”
Section: Disadvantages Of Automated Essay Scoring (Aes) Systemsmentioning
confidence: 99%